2004
DOI: 10.1177/000348940411301105
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic and Functional Long-Term Results of Canal Wall-Down Mastoidectomy

Abstract: The objective of this study was to evaluate, over the long-term, the anatomic and functional outcome of canal wall-down mastoidectomy performed for chronic otitis media with cholesteatoma and chronic otomastoiditis resistant to all conservative treatment. The study was made through a retrospective review of 338 cases of consecutive primary canal wall-down mastoidectomies performed between 1974 and 1998. Included were 259 cases with sufficient data. In all cases, functional reconstruction was performed at the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 14 publications
2
38
2
1
Order By: Relevance
“…In contrast, none of the patients required revision meatoplasty after performing our novel technique. In addition, the rate of postoperative infection was not significantly different from the rate for conventional meatoplasty (1.9 to 6.5%) found in a previous report (11). Furthermore, in cases in which revision canaloplasty or CWD were required for stenosis of the EAC, or in cases of recurrent infection after conventional meatoplasty, correction of the stenosis and a good cosmetic outcome were obtained by applying our PPF technique.…”
Section: Discussioncontrasting
confidence: 69%
“…In contrast, none of the patients required revision meatoplasty after performing our novel technique. In addition, the rate of postoperative infection was not significantly different from the rate for conventional meatoplasty (1.9 to 6.5%) found in a previous report (11). Furthermore, in cases in which revision canaloplasty or CWD were required for stenosis of the EAC, or in cases of recurrent infection after conventional meatoplasty, correction of the stenosis and a good cosmetic outcome were obtained by applying our PPF technique.…”
Section: Discussioncontrasting
confidence: 69%
“…It is worth mentioning that patients received PORP had better outcomes than those receiving TORP due to the effect of stapes suprastructures on the hearing outcome. (23,24) Nevertheless, De Corso et al [20] reported no effect of stapes suprastructures on hearing gain. It should be noted that reconstruction of the posterior canal wall remains a difficult procedure that requires surgical skill.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, second-look surgery is suggested after ICW mastoidectomy concurrent with tympanoplasty. [32,33] Dornhoffer [3] defended the idea that likely residual cholesteatoma should be considered in the event the disease became prominent in the anterior, or if conduction hearing loss is increased after posterior cartilage membrane reconstruction. In that study, the author determined the recurrence rate to be lower than 10% during the mean four-year follow-up period after tympanic membrane reconstruction performed by palisade technique in cholesteatoma surgery.…”
Section: Discussionmentioning
confidence: 99%